2011
DOI: 10.1016/j.agwat.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of domestic wastewater treated in macrophyte ponds to irrigate tomato and eggplant in semi-arid West-Africa: Benefits and risks

Abstract: a b s t r a c tThe scarcity of freshwater resources is a critical problem in semi-arid zones and marginal quality water is increasingly being used in agriculture. This paper aimed at evaluating the physico-chemical and biological risks on irrigated soils and fruits of macrophyte treated wastewater (TWW), the nutrients supply, and the effect on tomato and eggplant production in semi-arid Burkina Faso. During three years of experiments, treated wastewater was used, with fresh water as control, in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 13 publications
4
29
0
5
Order By: Relevance
“…According to Kiziloglu et al (2007), wastewater has a high nutritive value that may improve plant growth, reduce fertilizer application rates, and increase productivity of poor fertility soils. Diverse studies have indeed shown that TWW irrigation increases soil organic matter (Mañas et al 2009;Jueschke et al 2008;Kiziloglu et al 2007) as well as the concentrations of different nutrients involved in plant growth such as nitrogen (N), phosphorus, iron, manganese, potassium, calcium, magnesium, and others (Akponikpe et al 2011;Rezapour and Samadi 2011;Sacks and Bernstein 2011;Mañas et al 2009;Gwenzi and Munondo 2008;Kim et al 2007; Kiziloglu et al 2007;Angin et al 2005). Conversely, the use of TWW for irrigation can have detrimental effects on soil quality.…”
Section: Wastewater Reuse In Agriculture: Benefits Vs Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kiziloglu et al (2007), wastewater has a high nutritive value that may improve plant growth, reduce fertilizer application rates, and increase productivity of poor fertility soils. Diverse studies have indeed shown that TWW irrigation increases soil organic matter (Mañas et al 2009;Jueschke et al 2008;Kiziloglu et al 2007) as well as the concentrations of different nutrients involved in plant growth such as nitrogen (N), phosphorus, iron, manganese, potassium, calcium, magnesium, and others (Akponikpe et al 2011;Rezapour and Samadi 2011;Sacks and Bernstein 2011;Mañas et al 2009;Gwenzi and Munondo 2008;Kim et al 2007; Kiziloglu et al 2007;Angin et al 2005). Conversely, the use of TWW for irrigation can have detrimental effects on soil quality.…”
Section: Wastewater Reuse In Agriculture: Benefits Vs Risksmentioning
confidence: 99%
“…Perhaps the most evident public health qualms are linked to the presence pathogens. Several studies have reported high count of total coliforms and fecal coliforms in crops irrigated with TWW (Akponikpe et al 2011;Sacks and Bernstein 2011;Mutengu et al 2007;Rai and Tripathi 2007), while others have detected bacterial pathogens such as Salmonella, Streptococci, Clostridium, Shigella, and Vibrio spp. (Mañas et al 2009;Samie et al 2009).…”
Section: Wastewater Reuse In Agriculture: Benefits Vs Risksmentioning
confidence: 99%
“…The incensements in the seedling height were 69% and 13% for A. ampliceps and A. origena, respectively, while seedling diameter was 13% and 5.5% for A. ampliceps and A. origena, respectively, in the PTWR treatment than in the MW treatment. Several studies have also showed increasing in the growth parameters of trees and crops after irrigation with treated wastewater (Kiziloglu et al, 2008;Bedbabis et al, 2010;Akponikpèa, 2011;Pandey andSrivastava, 2012, andSelahvarzi andHosseini, 2012). Moreover, Carvalho et al (2012) found that the height and nodulation of Leucaena leucocephala and Mimosa caesalpiniaefolia significantly increased when treated with sewage effluent and inoculated with Rhizobium.…”
Section: Results and Discussion 1 Growth And Nodulation Of Acacia Spmentioning
confidence: 99%
“…It is believed that soon, wastewater treatment levels will be also dictated by the requirements of local recipients and not only by some general regulations [27]. The methods for evaluating the overall design and operation of wastewater treatment systems are therefore important for both economic and environmental considerations [28].…”
Section: Wastewater Reclamation Criteriamentioning
confidence: 99%